Contribution of shaded coffee plantations to bat conservation in la Antigua Guatemala, Guatemala - Kraker-Castañeda, Cristian; Pérez-Consuegra, Sergio Guillermo (Instituto de Ecología, A.C., 2011)
We studied bats in shaded coffee plantations and a forest remnant in the mountains around the valley of La Antigua Guatemala. We carried out a mist netting effort of 2880 m2h in each habitatand captured a total of 182 from 12 species. The number of species observed at each habitat was smaller than the non parametric Chao 2 estimator, 89% for the coffee plantations and 86% for the forest remnant, but close to the 90% satisfactory level. In the coffee plantations generalist species such as Artibeus, Dermanura and Sturnira dominated the bat assemblage, while species such as Phyllostomus discolor and Myotis keaysi were observed only in the forest remnant. There were no statistically significant differencesin Shannon diversity (H’) between habitats (t = -0.1442, g. l. = 133.83, p = 0.88), nevertheless forests showed a more even distribution of functional guilds in terms of percent of bats captured. There were statistically significant differences of the relative abundance of the first five fruit bats ranking in sample size (G = 53.48, g. l. = 4, p < 0.001). Forest remnants showed a significant greater representation of functional guilds different of fruit bats (G = 11.06, g. l. = 1, p < 0.001). We established a significant greater proportion of large bats in coffee plantations and a greater proportion of small bats in the forest remnant (G = 36.61, g. l. = 1, p < 0.001). The species complementarity (C) index between habitats was 42%, allowing us to question the possible function of the coffee plantations as corridors between forest remnants. The estimated richness with the study method is 17 species and we perceived 71% of this estimation.